2012
DOI: 10.1016/j.humimm.2012.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Nomenclature for factors of the HLA system, update January 2012

Abstract: The antigen-presenting cell–expressed CD40 is implied in the regulation of counteractive immune responses such as induction of pro-inflammatory and anti-inflammatory cytokines interleukin (IL)–12 and IL-10, respectively. The mechanism of this duality in CD40 function remains unknown. Here, we investigated whether such duality depends on ligand binding. Based on CD40 binding, we identifed two dodecameric peptides, peptide-7 and peptide-19, from the phage peptide library. Peptide-7 induces IL-10 and increases Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…During leishmanial infection, CD40 signaling is skewed toward the anti-inflammatory pathways involving cRaf, Syk, MEK1/2, ERK1/2, PKCδ, and PKCζ. However, stimulation with CD40L results in the skewing of the signaling toward pro-inflammatory pathway involving Lyn, PI3K, MKK3/6, p38, PKCα, and PKCβII ( Awasthi et al., 2003 ; Khan et al., 2012 , 2014 ; Mathur et al., 2004 ; Murugaiyan et al., 2006 ; Rub et al., 2009 ; Sudan et al., 2012 ). In addition, it was shown that LMP-1, a protein encoded by Epstein-Barr virus signaling like CD40, rescued certain functions—but not the full range—associated with the CD40 in CD40 −/− mice suggesting that there existed CD40L residue-specific signaling and functions ( Uchida et al., 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…During leishmanial infection, CD40 signaling is skewed toward the anti-inflammatory pathways involving cRaf, Syk, MEK1/2, ERK1/2, PKCδ, and PKCζ. However, stimulation with CD40L results in the skewing of the signaling toward pro-inflammatory pathway involving Lyn, PI3K, MKK3/6, p38, PKCα, and PKCβII ( Awasthi et al., 2003 ; Khan et al., 2012 , 2014 ; Mathur et al., 2004 ; Murugaiyan et al., 2006 ; Rub et al., 2009 ; Sudan et al., 2012 ). In addition, it was shown that LMP-1, a protein encoded by Epstein-Barr virus signaling like CD40, rescued certain functions—but not the full range—associated with the CD40 in CD40 −/− mice suggesting that there existed CD40L residue-specific signaling and functions ( Uchida et al., 1999 ).…”
Section: Introductionmentioning
confidence: 99%